Innovations in the Teaching of Instrumental Performance and Ensemble Science in Higher Education and the Use of Advanced Foreign Experience - Hayotbek Bazarov Ne’matovich (International Journal on Integrated Education, 2021)
The performance of a musician who does not work on himself on a regular basis can end quickly. Because this activity is a creative activity. Creative activity requires constant research and regular practice of performance skills. Therefore, by itself, not only in the learning process, but also until the end of the executive activity, the importance of gamma, trinity, and exercise remains the same. If we look at the activities of famous musicians, we can clearly see proof of this. In the article, the author provides a broad and clear understanding of the innovations in the teaching of instrumental performance and ensemble science in higher education and the use of advanced foreign experience.